PERAN GURU PAI DALAM MENGEMBANGKAN PENDIDIKAN MULTIKULTURAL UNTUK MENUMBUHKAN SIKAP TOLERANSI SISWA DI PESANTREN - Zahara Salma; Camelia; Husnul Mardiyah Daulay; Mutiah Nasution; Nurmarito Rambe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to comprehensively analyze the role of Islamic Religious Education (PAI) teachers in developing multicultural education to foster students' tolerance attitudes in Islamic boarding schools (pesantren). Tolerance is a fundamental value in Indonesia's pluralistic society, and pesantren as Islamic educational institutions bear great responsibility in instilling such values. This research employs a qualitative approach with in-depth interview methods involving PAI teachers and participant observation in pesantren environments. The results show that teachers play a strategic role in integrating multicultural values through moral and faith-based learning (akidah akhlak), inclusive teaching methods, and exemplary behavior in daily life. Values such as tolerance, equality, and mutual respect are instilled both inside and outside the classroom through various pedagogical approaches. The findings also indicate significant changes in students' attitudes from being initially exclusive and grouping based on regional backgrounds to becoming more open, inclusive, and respectful of differences. This success is inseparable from teacher commitment, curriculum support, and a conducive pesantren environment. Therefore, multicultural education implemented by PAI teachers is proven effective in fostering students' tolerance attitudes in pesantren environments.